Telaah Nilai-nilai Moderasi Beragama yang Terkandung Dalam Film Ayat-Ayat Cinta 2 - Muhamad Rouf Didi Sutriadi; M Jia Ulhaq (Seutia Hukamaa Cendekia, 2023)
The film ayat-2 is a film that was translated from a novel by Habiburrahman El Shirazy with the same title. This research examined the values ​​of religious moderation contained in the film. The researcher observes and describes the film Ayat-ayat Cinta 2 to obtain a more comprehensive analysis. The researcher also uses the theory of religious moderation used by the Ministry of Religion to analyze the film. After that, the researcher mapped out several scenes containing religious moderation values. The results of this study researchers found four scenes that carry the value of religious moderation. First, the scene of Fahri helping Grandma Caterina by taking her to the place of worship of the Jews is included in the